Mode of formation of cryogenic cave carbonates: Experimental evidence from an Alpine ice cave - Spötl, Christoph; Koltai, Gabriella; Dublyansky, Yuri (Chemical geology, 2023)
Coarsely crystalline carbonates that formed cryogenically in caves (CCCcoarse for short) are important paleoenvironmental archives that provide evidence of former perennial ice deposits in currently ice-free caves and allow the timing of the past freezing conditions close to 0 °C in the subsurface to be determined. Despite their significance, the mode of formation of these deposits has never been observed in statu nascendi. We conducted a series of freezing experiments in an Alpine ice cave to test the conceptual model of CCCcoarse formation in freezing pools of water in perennial ice deposits. Our results document a number of features associated with the freezing of such confined water bodies, including ice bulging, cracking and episodic expulsion of water. These observations help explain the degassing of carbon dioxide required to maintain carbonate precipitation in these semi-closed pockets of slowly freezing water. Our experiments yielded a range of morphological types of cryogenic calcite crystals and aggregates comparable to those reported from CCCcoarse from currently ice-free caves elsewhere. The experimentally grown crystals also exhibit the same depleted O isotope composition characteristic of natural carbonates interpreted as being formed subaqueously in a semi-closed pools subject to freezing. The main difference to naturally formed CCCcoarse is their smaller crystal size, reflecting the comparably short freezing time of our experiments of less than two weeks. This study confirms the conceptual model explaining the formation of CCCcoarse in localized pools in ice and calls for a revision of the currently existing classification scheme for cryogenic cave carbonates.